2020
DOI: 10.2298/pac2003260s
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dielectric properties of Sm3+ modified Bi4Ti3O12- SrBi4Ti4O15 intergrowth ferroelectrics

Abstract: Novel samarium modified intergrowth ferroelectric ceramics, namely Bi 4 Ti 3 O 12 -SrBi 4 Ti 4 O 15 , were synthesized by conventional solid state reaction method and sintered at 1100°C for 5 h. X-ray diffraction studies revealed the formation of a single phase with the signature of intergrowth oxide and plate like morphology was observed by scanning electron microscopic analyses. The orthorhombicity, the grain size and transition temperature were found to decrease with the increase of Sm content. The dielectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Finally, all the ordering of these materials tunes to multiferroic applications. The unsaturated and nonsymmetric nature of loops is associated with the leaky nature, on account of the high concentration of oxygen vacancies [7,17]. It is also observed that the coercive field and polarization increase with the applied voltages, as shown in Figure 5a-c.…”
Section: Ferroelectric Studiesmentioning
confidence: 84%
See 1 more Smart Citation
“…Finally, all the ordering of these materials tunes to multiferroic applications. The unsaturated and nonsymmetric nature of loops is associated with the leaky nature, on account of the high concentration of oxygen vacancies [7,17]. It is also observed that the coercive field and polarization increase with the applied voltages, as shown in Figure 5a-c.…”
Section: Ferroelectric Studiesmentioning
confidence: 84%
“…The intergrowth of the BLSFEM compound consists of one unit cell of one-half the unit cell of m-layered and the other half unit cell of (m + 1) layered compounds along the c-axis [6,17]. Earlier we reported the electrical properties of intergrowth of Sm-modified Bi 4 Ti 3 O 12 and SrBi 4 Ti4O 15 [17]. The XRD pattern of intergrowth is well indexed with the SrBi 8 Ti 7 O 27 (eight layers) compound.…”
Section: Introductionmentioning
confidence: 99%
“…Here in this perovskite layers A = Bi 3+ and B = Fe 3+ , Ti 4+ and n in (A n − 1 B n O 3 n + 1 ) 2− refers to the number of perovskite‐like packets between the Bi 2 O 2 layers 77‐79 . A combination of 1 mol of a three‐layered monoclinic Bi 4 Ti 3 O 12 and m moles of rhombohedral perovskite BiFeO 3 , with m = 1, 2, and 5, are considered as four‐, five‐, and eight‐layered compounds: Bi 5 FeTi 3 O 15 , Bi 6 Fe 2 Ti 3 O 18 , and Bi 9 Fe 5 Ti 3 O 27 and these are simultaneously ferroelectric and AFE in nature 80 . Due to coexistence of ferroelectric and magnetic ordering these are candidate materials for magnetoelectric applications.…”
Section: Aurivillius Phase Ferroelectric Thin Filmsmentioning
confidence: 99%
“…[77][78][79] A combination of 1 mol of a three-layered monoclinic Bi 4 Ti 3 O 12 and m moles of rhombohedral perovskite BiFeO 3 , with m = 1, 2, and 5, are considered as four-, five-, and eight-layered compounds: Bi 5 FeTi 3 O 15 , Bi 6 Fe 2 Ti 3 O 18 , and Bi 9 Fe 5 Ti 3 O 27 and these are simultaneously ferroelectric and AFE in nature. 80 Due to coexistence of ferroelectric and magnetic ordering these are candidate materials for magnetoelectric applications. Lead-free and fatigue free ferroelectric aurivillius oxides with unmatched fatigue resistance are attributed to their unique crystalline structure with perovskite-like slabs with inter growth of (Bi 2 O 2 ) 2+ layers act as barriers to inhibit the long-range diffusion of space charges and defects, which are generated during the domain wall motion and form the electrode-ferroelectric interface.…”
Section: Aurivillius Phase Ferroelectric Thin Filmsmentioning
confidence: 99%